ANALYSIS OF THE PREVALENCE OF ALCOHOL CONSUMPTION IN HYPERTENSION PATIENTS AT THE GLENO INPATIENT PUBLIC HEALTH CENTER ERMERA MUNICIPALITY, TIMOR-LESTE - de Carvalho, Joaquin Gregorio; de Costa, Antonio; Soares, Domingos (Universitas Nahdlatul Ulama Surabaya, 2021)
Background; Arterial hypertension is a chronic disease where the blood pressure in the arteries is persistently above the normal value (systolic pressure > 140 mmHg or diastolic pressure is > 90 mmHg). The worldwide number of hypertension deaths reaches 9.4 million deaths. Hypertension data recorded at Gleno Inpatient Health Centre (IHC) in 2019 reaches 810 patients. Objective; This study aimed to analysis on alcohol consumption with prevalence of hypertension. Methods; This quantitative research used correlation approach, the samples were the patients who make an appointment and intern in Gleno IHC, the sampling technique was non-probability, the purposive sampling technique based of the inclusion criteria and the instrument was a questionnaire. Results; Sample size on study were 46 respondents. Based on the results of correlation statistical analysis Spearman Rank indicates the p-value was 0.001, which is lower than 0.05. This test showed a significant relationship between the consumption of alcohol with the occurrence of hypertension in Gleno IHC. Never the less, the result of the correlation test (r) was 0.473. Which means having the most high impact of alcohol consumption with an opportunity of 0.473 times. Which result in the most severe hypertension disease in Gleno IHC. Conclusion; This research indicated that the relationship is positive and significant between the alcohol consumption and the prevalence of hypertension in Gleno Inpatient Health Centre, municipality of Ermera. This result can be used as a good input to improve the health promotion program and better service for hypertension patients at this health centre.